Assessing the vulnerability of marine ecosystems in the Gulf of Tonkin to human impacts and climate change - natural disasters - Tran, Duc Thanh; Dang, Hoai Nhon; Bui, Van Vuong; Duong, Thanh Nghi; Nguyen, Dang Ngai; Cao, Thi Thu Trang; Vu, Duy Vinh (Vietnam Journal of Marine Science and Technology, 2026)
The Gulf of Tonkin (Vietnam part) comprises 12 typical marine ecosystems distributed across 7 ecological regions. Human activities impacting the marine ecosystems are classified into three groups: strong impacts (fishing, aquaculture, navigation - ports, and marine infilling); medium impacts (dredging - dumping, mining, tourism - services); and weak impacts (security - defense). Climate change and natural disasters affecting marine ecosystems are categorized into three impact groups. The strong impact group includes water temperature, typhoons, waves, and rising sea levels. The medium impact group consists of turbidization, local freshening, salinization, and erosion. The low-impact group comprises circulation disturbances and sedimentation. The vulnerability of marine ecosystems, influenced by human activities, climate change, and natural disasters, varies and is classified into three levels. Highly vulnerable areas include lagoons, estuarine areas, tidal flats, seagrass beds, and coral reefs. The medium vulnerability encompasses ecosystems such as beaches, mangrove forests, and permanent wetlands. Low vulnerability encompasses ecosystems such as the seafloor, marine lakes, rocky coasts, and upwelling areas. Ecological zones with a high vulnerability levels include the coastal marine zones of Mong Cai - Do Son (Z.1) and Mui Roon - Hai Van (Z.4). The zones with medium vulnerability levels include the coastal marine zones of Do Son - Lach Truong (Z.2) and Lach Truong - Mui Roon (Z.3). In contrast zones with a low vulnerability levels include the northern marine zones of the Gulf (Z.5), the middle marine zone of the Gulf (Z.6), and the southern marine zone of the Gulf (Z.7).